2003
DOI: 10.1186/1471-2091-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation impact on the catalytic activities of the mitochondrial D-3-hydroxybutyrate dehydrogenase in liver and brain tissues of jerboa (Jaculus orientalis)

Abstract: BackgroundJerboa (Jaculus orientalis) is a deep hibernating rodent native to subdesert highlands. During hibernation, a high level of ketone bodies i.e. acetoacetate (AcAc) and D-3-hydroxybutyrate (BOH) are produced in liver, which are used in brain as energetic fuel. These compounds are bioconverted by mitochondrial D-3-hydroxybutyrate dehydrogenase (BDH) E.C. 1.1.1.30. Here we report, the function and the expression of BDH in terms of catalytic activities, kinetic parameters, levels of protein and mRNA in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our previous studies have shown that prehibernation of jerboas is associated with hypotriglyceridemia and hypoketonemia, which result from a high rate of fatty acid and triacylglycerol uptake concomitant with depressed mitochondrial and peroxisomal fatty acid oxidation in adipose tissues (27,28). We have also reported the participation of jerboa PPAR isotypes b/d and g in brown fat non-shivering thermogenesis and in white fat adipogenesis during hibernation bouts, respectively (28).…”
Section: Discussionmentioning
confidence: 89%
“…Our previous studies have shown that prehibernation of jerboas is associated with hypotriglyceridemia and hypoketonemia, which result from a high rate of fatty acid and triacylglycerol uptake concomitant with depressed mitochondrial and peroxisomal fatty acid oxidation in adipose tissues (27,28). We have also reported the participation of jerboa PPAR isotypes b/d and g in brown fat non-shivering thermogenesis and in white fat adipogenesis during hibernation bouts, respectively (28).…”
Section: Discussionmentioning
confidence: 89%
“…The loss of important enzymes in EVs shed by APAP-treated rat livers, which are involved in the metabolism of xenobiotics, such as cytochromes P450, cytochrome b5, and cytochrome b5 reductase, is an indication of severe oxidative stress [ 103 ]. Furthermore, the loss of UGT enzymes that play a key role in the elimination of xenobiotics is also an additional sign of severe cellular stress [ 20 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%